2020
DOI: 10.1007/s11307-020-01499-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Human Embryonic Stem Cell-Derived Dopaminergic Neuron Progenitor Transplants Using Non-invasive Imaging Techniques

Abstract: Purpose Human pluripotent stem cell (hPSC)-derived dopaminergic neuron progenitor cells (DAPCs) are a potential therapy for Parkinson’s disease (PD). However, their intracranial administration raises safety concerns including uncontrolled proliferation, migration and inflammation. Here, we apply a bimodal imaging approach to investigate the fate of DAPC transplants in the rat striatum. Procedures DAPCs co-expressing luciferase and ZsGreen or labelled with micron-sized particles of iron oxide (MPIOs) were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Dr. Shugo Tohyama (Department of Cardiology, Keio University School of Medicine, Japan) addressed challenges for the manufacture of ventricular cardiomyocyte‐like cells from hiPSCs for the treatment of severe cardiac failure. 14 Dr. Tohyama focused his presentation on issues of cardiomyocyte purity and potential tumorigenicity due to residual undifferentiated iPSCs that, even at levels of 0.02% of cells, were able to form teratomas in animals and were therefore a possible risk to patients. First, he described a means of regulating the metabolism of differentiated cell preparations using a glucose and glutamine‐depleted media supplemented with lactate to eliminate undifferentiated hPSCs.…”
Section: Analytical Methods and Releasementioning
confidence: 99%
“…Dr. Shugo Tohyama (Department of Cardiology, Keio University School of Medicine, Japan) addressed challenges for the manufacture of ventricular cardiomyocyte‐like cells from hiPSCs for the treatment of severe cardiac failure. 14 Dr. Tohyama focused his presentation on issues of cardiomyocyte purity and potential tumorigenicity due to residual undifferentiated iPSCs that, even at levels of 0.02% of cells, were able to form teratomas in animals and were therefore a possible risk to patients. First, he described a means of regulating the metabolism of differentiated cell preparations using a glucose and glutamine‐depleted media supplemented with lactate to eliminate undifferentiated hPSCs.…”
Section: Analytical Methods and Releasementioning
confidence: 99%
“…Alternative current approaches are focused on the development of multimodal imaging platforms, combining bioluminescence imaging with increasingly sensitive techniques such as MRI. Such bi-modal imaging platforms could present a comprehensive method for assessing the safety and efficacy of cell-based therapies in preclinical models 157 160 .…”
Section: Manufacturing Storage and Testingmentioning
confidence: 99%
“…FGF signaling is triggered using the recombinant protein FGF8b ( Figure 2 ). This combination results in a high yield of vmDA progenitor cells capable of differentiating into vmDA neurons ( Cai et al, 2010 ; Kriks et al, 2011 ; Doi et al, 2012 ; Sanchez-Danes et al, 2012 ; Doi et al, 2014 ; Grealish et al, 2014 ; Grealish et al, 2015 ; Samata et al, 2015 ; Steinbeck et al, 2015 ; Samata et al, 2016 ; Adil et al, 2017 ; Niclis et al, 2017 ; Nolbrant et al, 2017 ; Wakeman et al, 2017 ; Xia et al, 2017 ; Fathi et al, 2018 ; Adler et al, 2019 ; Chang et al, 2019 ; Zygogianni et al, 2019 ; Mousavinejad et al, 2020 ; Schweitzer et al, 2020 ; Song et al, 2020 ; Kim T. W. et al, 2021 ; Xiong et al, 2021 ). Researchers like Perrier and his colleagues have focused on differentiation using SHH and FGF8 and found that approximately 60%–80% of beta tubulin III (TUJ1)-positive neurons express TH ( Perrier et al, 2004 ).…”
Section: Advances In Hpsc-derived Da Progenitor Transplantation Resea...mentioning
confidence: 99%